Health benefits of Stevia rebaudiana Bertoni as zero calorie natural sweetener: a review - Zainol, Haida; A., Asikin; Awang @ Mansor, Mohd Hakiman (Universiti Putra Malaysia, 2020)
Stevia rebaudiana Bertoni is a perennial herbal species with a number of therapeutic properties. The leaves of S. rebaudiana are the most important part of the plant as they contain high level of sweetener compounds known as steviol glycosides; which are known to possess antioxidant, antimicrobial, and antifungal activities. Among the steviol glycosides, stevioside and rebaudioside A are the most abundant sweetening compounds of interest, documented to be 30 - 250 folds sweeter than sucrose or refined sugar. The therapeutic properties of the species make it more interesting as they play important roles as anti hyperglycaemic agent to lower glucose levels in the blood, thus commonly used in the treatment of diabetes mellitus and obesity. Known to have sweet tasting leaves, its extract which contains antioxidant compounds have been used to treat cancer, reduce inflammatory, and hypertension. S. rebaudiana has drawn the attention of health-conscious fitness lovers all over the world as non-caloric sweetener, and has been widely cultivated for being the most suitable sweetening substitution.